2019
DOI: 10.1136/jech-2018-210627
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental chemicals and type 1 diabetes: an update

Abstract: This narrative review summarises recently published epidemiological and in vivo experimental studies on exposure to environmental chemicals and their potential role in the development of type 1 diabetes mellitus (T1DM). These studies focus on a variety of environmental chemical exposures, including to air pollution, arsenic, some persistent organic pollutants, pesticides, bisphenol A and phthalates. Of the 15 epidemiological studies identified, 14 include measurements of exposures during childhood, 2 include p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Lut has a defensive activity contradicted to the damage because of OS in specific organs, for example, the kidney, the heart, and the liver. Past investigations have proven that Lut could prevent hepatotoxicity caused by the administration of BPA, by diminishing OS and inflammation by means of blocking NF‐κB incitement . OS means that tissue damage brings about by BPA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Lut has a defensive activity contradicted to the damage because of OS in specific organs, for example, the kidney, the heart, and the liver. Past investigations have proven that Lut could prevent hepatotoxicity caused by the administration of BPA, by diminishing OS and inflammation by means of blocking NF‐κB incitement . OS means that tissue damage brings about by BPA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental chemicals have been suggested to influence type 1 diabetes by various mechanisms, but there are few high quality studies of human type 1 diabetes. 142 A few studies have found suggestive evidence for an association between air pollution and risk of type 1 diabetes, but there are methodological difficulties with exposure measurements. Overall, there seem to be no consistent association between environmental toxins and type 1 diabetes, or islet autoimmunity.…”
Section: Toxinsmentioning
confidence: 99%
“…Overall, there seem to be no consistent association between environmental toxins and type 1 diabetes, or islet autoimmunity. 142,143 Although many toxins have been introduced into the environment, many have been banned resulting in decreasing exposure trends. 144 Air pollution is highest in areas with low incidence of type 1 diabetes and has decreased over the past decades in high-income countries.…”
Section: Toxinsmentioning
confidence: 99%
“…Research on environmental factors involved in the etiology of islet autoimmunity were focused on the role of viruses [20,21], early infant diet [22,23], childhood weight gain [24], vitamin D [25], gut microbiome [26][27][28], and environmental endocrine disrupting chemicals (EDCs) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%